Product Differentiation Strategies in Indonesian Green MSMEs: An Integrated Marketing Mix Analysis - Andriani, Nukeu Novia; Hurriyati, Ratih; Dirgantari, Puspo; Gaffar, Vanessa (Ilomata International Journal of Management, 2026)
This study investigates product differentiation strategies employed by Indonesian green Micro, Small, and Medium Enterprises (MSMEs) through qualitative descriptive methodology. Semi-structured interviews were conducted with founder-owners of five green MSMEs in fashion and handicraft sectors across Java, analyzed using thematic coding (Braun & Clarke, 2006), SWOT-IFE/EFE evaluation, and QSPM prioritization. Findings revealed that effective differentiation requires holistic integration across Marketing Mix elements, characterized by three core dimensions: universal natural and upcycled material sourcing (100% adoption), premium pricing with 2 to 5 times markups, and export-oriented positioning with 70 to 90 percent international revenue. Strategic analysis positioned enterprises in the "Hold and Maintain" quadrant (IFE = 2.63; EFE = 2.55), suggesting selective growth. The study identifies three structural paradoxes constraining development: certification barriers, premium pricing traps excluding mass markets, and digital hesitancy limiting e-commerce engagement. Strategic priorities include Green Export Acceleration (TAS 2.60), National Standard Harmonization with Subsidized Certification (TAS 2.54), and Tiered Product Development (TAS 2.52). These findings extend differentiation theory (Porter, 1985; Barney, 1991) by demonstrating that resource constraints fundamentally alter differentiation mechanisms for green enterprises in emerging economies.